Ontology-Based Sentence Extraction for Answering Why-Question - A. A. I. N. Eka Karyawati; Edi Winarko; Azhari Azhari; Agus Harjoko (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Most studies on why-question answering system usually   used   the   keyword-based   approaches.   They   rarely involved domain ontology in capturing the semantic of the document contents, especially in detecting the presence of the causal relations. Consequently, the word mismatch problem usually  occurs  and  the  system  often  retrieves  not  relevant answers. For solving this problem, we propose an answer extraction method by involving the semantic similarity measure, with selective causality detection. The selective causality detection is  applied  because  not  all  sentences  belonging  to  an  answer contain  causality.  Moreover,   the   motivation  of  the  use  of semantic similarity measure in scoring function is to get more moderate results about the presence of the semantic annotations in a sentence, instead of 0/1. The semantic similarity measure employed is based on the shortest path and the maximum depth of the ontology graph. The evaluation is conducted by comparing the proposed method against the comparable ontology-based methods, i.e., the sentence extraction with Monge-Elkan with 0/1 internal similarity function. The proposed method shows the improvements in  term of  MRR (16%, 0.79-0.68), P@1  (15%, 0.76-0.66), P@5 (14%, 0.8-0.7), and Recall (19%, 0.86-0.72).